Species’ cultural heritage inspires a conservation ethos: The evidence in black and white - Hopper, NG; Gosler, AG; Sadler, JP; Reynolds, SJ (Wiley, 2019)
Birds feature prominently in the arts and folklore of practically every culture. Yet, in industrialized countries, this rich cultural heritage is largely ignored by conservation biologists. Taking the Eurasian Magpie (Pica pica) as a focal species, we conducted a classroom‐based survey to test the value of avian cultural heritage for inspiring a conservation ethos among UK schoolchildren, comparing it with the effects of other information types and factors. Although identified effects were not strong, species’ cultural heritage was found to be valued and a positive driver of conservation concern—one, we suggest, that has the potential to endure into adulthood when certain other conservation motivations may fail. We therefore encourage its more widespread incorporation into conservation education and outreach programs. Our findings constitute an important “first word” on the potential value of species’ cultural heritage for inspiring a lasting conservation ethos.